Antibacterial activity of methanolic extracts from sea cucumber (Pattalus mollis) against pathogenic bacteria - Díaz-Sol Sol, Katia (2019)
The aim of this study was to evaluate the antibacterial activity of methanol and methanol-chloroform extracts of tegument, gonad and viscera of Pattalus mollis. Fifty specimens were collected in the Pucusana Bay, Peru, dissected longitudinally through the ventral area of ​​the tegument and the internal organs (viscera, gonad) were removed. The samples were dried to 10% moisture, milled and stored in freezing. The extracts were obtained by maceration using methanol and chloroform. The in vitro evaluation was performed using the broth microdilution method, the extracts were diluted in seven concentrations (3.9-250 mg/ml) and evaluated against Pseudomonas aeruginosa ATCC 27853, Staphylococcus aureus ATCC 14775 and Vibrio alginolyticus ATCC 17749. The methanol extract showed bacterial inhibition against the three bacteria, demonstrating a bactericidal and bacteriostatic effect against Gram-positive and Gram-negative bacteria. The viscera, gonad and tegument extracts showed a minimum inhibitory concentration (MIC) of 62.5 mg/ml or higher against P. aeruginosa, V. alginolyticus and S. aureus. The results suggest that sea cucumber P. mollis, from the Peruvian coasts, is a novel candidate to produce antibacterial compounds.